Evaluation of a compact VUV spectrometer for elemental imaging by laser-induced breakdown spectroscopy: application to mine core characterization. Issue 8 (7th July 2017) - Trichard, F.; Moncayo, S.; Devismes, D.; Pelascini, F.; Maurelli, J.; Feugier, A.; Sasseville, C.; Surma, F.; Motto-Ros, V.
Abstract : This work introduces a new approach to perform LIBS elemental imaging in the vacuum ultraviolet (VUV) wavelength range by using an argon purged probe coupled to a compact spectrometer. Abstract : This work introduces a new approach to perform LIBS elemental imaging in the vacuum ultraviolet (VUV) wavelength range by using an argon purged probe coupled to a compact spectrometer. In spite of several important elements for geological and industrial applications such as S, P, As, B, C, or Zn presenting strong lines in the VUV range, the need for using specific optics and working under oxygen-free conditions has limited the extension of LIBS systems available for such a range. Herein, we present an adaptation of our LIBS imaging instrumentation to access the VUV while operating under ambient conditions. The proposed detection system is based on an optical probe directly coupled to a Maya2000Pro compact spectrometer (Ocean Optics), all purged with argon. The technical design along with a detailed evaluation of the VUV probe is addressed. The possibility of using this VUV probe for LIBS imaging is also investigated by studying a Canadian mine core sample with special emphasis on the detection of sulfur. In addition to sulfur, more than 15 elements including P, As, C, Ca, Si, Mo, B, and Zn have also been detected. Elemental images covering sample surfaces in the range of cm 2 with a micrometric spatial resolution (10 μm) are presented. A detection limit of 0.2 wt% for sulfur is demonstrated in a single shot configuration. These results open new perspectives for both conventional LIBS and LIBS-based imaging in various application fields.